The redistribution recession how labor market distortions contracted the economy - Mulligan, Casey B. (New York ; Oxford : Oxford University Press, 2013)
This title is a controversial, clear-cut, and thoroughly researched analysis of the effects of various government policies on the labour market during the recent recession.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Labor market -- United States -- 21st century; Recessions -- United States -- History -- 21st century; Income distribution -- United States -- History -- 21st century